The Role of Informed Consent in the Legality and Legal Protection of Medical Personnel - Danetsye Samallo; Yana Chaeru Taufik Ismail (Research Horizon, 2026)
Medical professionals face litigation risks from legal uncertainty in medical procedures, highlighting informed consent as an important legal protection amid rising medical disputes in Indonesia. The purpose of this research is to analyze the role of informed consent in ensuring the legality of medical procedures, examine its legal construction as a basis for excluding criminal liability for medical personnel under Law Number 17 of 2023 concerning Health, and assess its application in digital health services and high-risk medical procedures. The research method used is normative juridical with a statute approach and a conceptual approach. The results of the study indicate that informed consent is not merely an administrative formality, but rather the primary legal basis that transforms invasive procedures into legally valid actions by fulfilling patient autonomy. Legally, informed consent functions as a justification (rechtvaardigingsgronden) that eliminates the material unlawfulness of medical procedures, as long as they are carried out according to professional standards and without information defects (vitiated consent). This study concludes that informed consent is an essential preventive legal protection instrument that eliminates criminal culpability through the principle of volenti non fit iniuria, provided that medical information is communicated effectively.